1990
DOI: 10.1139/x90-071
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fire on the vegetation of Siberian taiga predominated by Larixdahurica

Abstract: In the summer of 1988, a vegetation survey of the Siberian taiga was conducted in a discontinuous permafrost zone of northern China where a destructive fire had occurred in the spring of 1987. The dominant forest cover of this area was larch, with spruce forests occurring in wet valleys and pine forests on steep, dry slopes. The vertical structure of forests showed that the spruce forests were preceded by larch forests; however, most of the larch forests were self-renewable probably because their habitats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Although fire is a controlling factor for the Larix forests of the Da Xingan Ling Mts. of northeastern China (Zheng et al 1986(Zheng et al , 1990Uemura et al 1990), many mature and old-growth Larix forests can still be found. Trees in these forests die by snapping, uprooting or while standing (Ban 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Although fire is a controlling factor for the Larix forests of the Da Xingan Ling Mts. of northeastern China (Zheng et al 1986(Zheng et al , 1990Uemura et al 1990), many mature and old-growth Larix forests can still be found. Trees in these forests die by snapping, uprooting or while standing (Ban 1994).…”
Section: Introductionmentioning
confidence: 99%
“…This higher rate of recovery is probably due to their thick bark (Kozlowski set al 1991), which protects the cambium from fire (Kozlowski et al 1991;Uemura et al 1990). …”
Section: Resultsmentioning
confidence: 99%
“…Sprouting plays an important role in forest recovery and affects succession after fire (Viereck 1973). Many studies have examined sprouting ability with respect to species, individual size, and when the fire occurred (Kauffman 1991;Lloret et al 1999;López-Soria and Castell 1992;Masaka et al 2000;Trabaud and Lepart 1980;Uemura et al 1990). Of the various types of sprouting, root collar sprouting is a common means of regeneration after disturbance (e.g., Bellingham and Sparrow 2000;Kramer and Kozlowski 1979).…”
Section: Introductionmentioning
confidence: 99%
“…During the last glacial maximum, Hokkaido was largely dominated by boreal conifers including the deciduous conifer Larix (Tsukada 1983). The understory of larch forest was probably composed of many summergreen herbs, as the present vegetation of eastern Siberia where forest of the deciduous conifer Larix dahurica is the most dominant, and many summergreen herbs frequently occur in the understory (Uemura et al 1990). …”
Section: Discussionmentioning
confidence: 99%